Spectraphotometric determination of some local anesthetics - Yars, Ünal (Marmara Pharmaceutical Journal, 1988)
In this work, the determination of benzocaine, procaine hydrochloride, butacaine sulfate and tetracaine in injectious solutions containing thiamine hydrochloride and pyridoxine hydrochloride was performed at UV by absorbancy ratio method without prior seperation of the drugs.